Association of Physical Education with Improvement of Health-Related Physical Fitness Outcomes and Fundamental Motor Skills Among Youths: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (American Medical Association, 2020)
Importance: Whether quality- or quantity-based physical education (PE) interventions are associated with improvement of health-related physical fitness outcomes and fundamental motor skills (FMSs) in children and adolescents is unknown. Objective: To examine the association of interventions aimed at optimizing PE in terms of quality (teaching strategies or fitness infusion) or quantity (lessons per week) with health-related physical fitness and FMSs in children and adolescents. Data Sources: For this systematic review and meta-analysis, studies were identified through a systematic search of Ovid MEDLINE, Embase, Cochrane Controlled Trials Registry, and SPORTDiscus databases (from inception to October 10, 2019) with the keywords physical education OR PE OR P.E. AND fitness AND motor ability OR skills. Manual examination of references in selected articles was also performed. Study Selection: Studies that assessed the association of quality- or quantity-based PE interventions with improvement in physical fitness and/or FMSs in youths (aged 3-18 years) were included. Data Extraction and Synthesis: Data were processed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Random-effects models were used to estimate the pooled effect size (Hedges g). Main Outcomes and Measures: Health-related physical fitness outcomes and FMSs. Results: Fifty-six trials composed of 48185 youths (48% girls) were included in the meta-analysis. Quality-based PE interventions were associated with small increases in health-related physical fitness (cardiorespiratory fitness [Hedges g = 0.24; 95% CI, 0.16-0.32] and muscular strength [Hedges g = 0.19; 95% CI, 0.09-0.29]) and FMSs (Hedges g = 0.38; 95% CI, 0.27-0.49). Subgroup analyses found stronger associations for quality-based PE interventions on body mass index (Hedges g = -0.18; 95% CI, -0.26 to -0.09), body fat (Hedges g = -0.28; 95% CI, -0.37 to -0.18), cardiorespiratory fitness (Hedges g = 0.31; 95% CI, 0.23-0.39), and muscular strength (Hedges g = 0.29; 95% CI, 0.18-0.39). Quantity-based PE interventions were associated with small increases in only cardiorespiratory fitness (Hedges g = 0.42; 95% CI, 0.30-0.55), muscular strength (Hedges g = 0.20; 95% CI, 0.08-0.31), and speed agility (Hedges g = 0.29; 95% CI, 0.07-0.51). Conclusions and Relevance: The findings suggest that quality-based PE interventions are associated with small increases in both student health-related physical fitness components and FMSs regardless of frequency or duration of PE lessons. Because PE aims to improve more than health, high levels of active learning time may need to be balanced with opportunities for instruction, feedback, and reflection. © 2020 American Medical Association. All rights reserved.